Strategi Komunikasi Pemasaran Kopi Kenangan (Studi Konten YouTube tentang Perkembangan Bisnis Kopi Kenangan) - Indah, Meutia; Saputra, Datep Purwa; Ayuna, Novianty Elizabeth (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to analyze Kopi Kenangan's marketing communication strategies through YouTube content, as well as to identify obstacles in consistently achieving the Top of Mind position in Indonesia's coffee shop market until 2025, considering fluctuations in its Top Brand Award index. This study employs a qualitative approach with a case study on Kopi Kenangan. Data were collected through triangulation: (1) an in-depth content analysis of three